2016
DOI: 10.1590/1516-3180.2016.0057180316
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure levels and body mass index in Brazilian adults with Down syndrome

Abstract: CONTEXT AND OBJECTIVE: Increased life expectancy among people with Down syndrome (DS) has introduced new environmental factors that may affect blood pressure (BP) and/or lead to obesity in this population. The aim here was to investigate BP levels and body mass index (BMI) in adults with DS, correlating these data with the patients' sex and age. DESIGN AND SETTING: Analytical cross-sectional observational study conducted in special schools in Curitiba (PR), Brazil. METHODS: 97 adult patients were included. BP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…18,19 Unlike the general population, however, individuals with DS have low prevalence of traditional vascular risk factors, such as hypertension, type 2 diabetes, and atherosclerosis. [20][21][22][23][24] Assessment of cerebrovascular changes in DS has been restricted primarily to the analysis of cerebral amyloid angiopathy (CAA), [25][26][27][28] attributed to the overproduction of amyloid. However, more comprehensive consideration of cerebrovascular changes among individuals with DS provides the unique opportunity to both characterize cerebrovascular biomarkers in vivo and study cerebrovascular disease in AD without the confound of vascular risk factors or advanced systemic arterial disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Unlike the general population, however, individuals with DS have low prevalence of traditional vascular risk factors, such as hypertension, type 2 diabetes, and atherosclerosis. [20][21][22][23][24] Assessment of cerebrovascular changes in DS has been restricted primarily to the analysis of cerebral amyloid angiopathy (CAA), [25][26][27][28] attributed to the overproduction of amyloid. However, more comprehensive consideration of cerebrovascular changes among individuals with DS provides the unique opportunity to both characterize cerebrovascular biomarkers in vivo and study cerebrovascular disease in AD without the confound of vascular risk factors or advanced systemic arterial disease.…”
mentioning
confidence: 99%
“…Vascular risk factors are associated with a higher risk of clinical AD and with AD biomarkers in later life 18,19 . Unlike the general population, however, individuals with DS have low prevalence of traditional vascular risk factors, such as hypertension, type 2 diabetes, and atherosclerosis 20–24 . Assessment of cerebrovascular changes in DS has been restricted primarily to the analysis of cerebral amyloid angiopathy (CAA), 25–28 attributed to the overproduction of amyloid.…”
mentioning
confidence: 99%
“…The PEH responses in individuals with DS are more related with BP regulation since most individuals with DS do not exhibit hypertension [30] or exhibit low BP [31].…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of overweight and obesity in adults with DS warrants attention. In a study conducted by Pucci et al 11 of 97 adults with DS, 40.7% were overweight and 37.4% were obese. The study found no significant differences for gender or age (18-56 years).…”
Section: Endocrine Diseasesmentioning
confidence: 95%